Alterações nas características da água de produção em processo de injeção de CO2 e recuperação de metano em camada de carvão - Costa, Gláucia dos Santos (2012)
The growing global economic development, followed by increased energy demand, interconnected on the dependence of fossil fuels, has contributed to an increased concentration of greenhouse gases in the atmosphere, mainly carbon dioxide (CO2). In this context, the Enhanced Coalbed Methane (ECBM) with CO2 injection technique, emerges as a promising proposal to alleviate this situation, because as is results in methane recovery (used for energy production) and storage of carbon dioxide (contributing to mitigating the greenhouse effect). This process involves production of formation water, which may contain numerous dissolved ions (Na+, Ca+2, Cl-, SO4-2) and trace elements. Therefore, study of this water and eventually treatment is necessary, this being one aspect that could undermine the application of this technology. Laboratory experiments were conducted to observe possible changes in the composition and properties of produced water generated during dewatering process with CO2 injection. Coal samples from the states of RS, SC and PR were analyzed. There was a high concentration of SO4-2 ions and the elements Fe, Zn, Al and Ni, in accordance with legislation, as well as high values of TDS (mgxL-1) for the field Leão - Butiá. It was concluded that there is a need for treatment of reclaimed water in a process of CBM/ECBM, for the fields analyzed because the limits established by law for the analyzed parameters are extrapolated.